Structural model reconstruction of transformational leadership and self-efficacy effects on teacher performance: a systematic review - Yudhi Hertanto; Widodo Widodo; Merry Lapasau; Bambang Sumadyo (Jurnal Konseling dan Pendidikan, 2026)
The nationwide digitalization of teacher administration through the integration of the Platform Merdeka Mengajar (PMM) and the e-Kinerja performance system has triggered unprecedented psychological pressures and administrative workloads, leading to fluctuations in teacher performance. This study aims to reconstruct an integrative conceptual model of the contributions of school principals' transformational leadership and teacher self-efficacy to teacher performance using a theory-building Systematic Literature Review (SLR) approach. Guided by the PRISMA 2020 protocol, a rigorous literature search was conducted on Scopus, Web of Science, and Sinta 1–3 databases to identify peer-reviewed original articles published between 2016 and 2026. Study quality was appraised using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist by two independent reviewers, achieving a highly reliable inter-rater agreement (κ=0.85). Qualitative-narrative synthesis of 38 selected articles demonstrates that transformational leadership has a consistently robust cumulative macro-effect correlation (r=0.441, p<0.001) on teacher performance. Furthermore, this study proves that self-efficacy does not merely act as a linear independent variable, but simultaneously functions as a cognitive mediator and contextual moderator (mediated-moderation) that dictates the direction and strength of leadership influence on performance. This reconstruction successfully resolves empirical gaps where the direct effect of transformational leadership was occasionally non-significant in micro-samples. This article formulates a novel structural model and four theoretical propositions to guide future primary quantitative research.